Brownian Tree‐Shaped Dendrites in Quasi‐2D Perovskite Films and Their Impact on Photovoltaic Performance (Adv. Mater. Interfaces 13/2022). Issue 13 (4th May 2022) - Zheng, Fei; Angmo, Dechan; Hall, Christopher R.; Rubanov, Sergey; Yuan, Fangfang; Laird, Jamie S.; Gao, Mei; Smith, Trevor A.; Ghiggino, Kenneth P.
Abstract : Dendrite Formation in Quasi‐2D Perovskite Films for Solar Cells In article number 2102231, Fei Zheng, Kenneth P. Ghiggino, and co‐workers report that Brownian tree‐shaped dendrites that form in quasi‐2D perovskite films are beneficial to perovskite solar cell performance. The dendrites are grown by the diffusion‐limited aggregation of thicker Ruddlesden‐Popper perovskite phase domains resulting in improved film morphology.